Prevalence of Fibromyalgia and Its Impact on General Health Among University Students - Minab Faisal; Zahid Mehmood; Ameena Amjad; Rubab Asif; Rabah Faisal; Raveena Rajpoot; Horria gondal (Journal of Health, Wellness and Community Research, 2026)
Background: Fibromyalgia is a chronic pain syndrome characterized by widespread musculoskeletal pain and multidimensional impairment, yet its burden in university populations remains underexplored. Objective: To evaluate the prevalence of fibromyalgia among university students and to measure its impact on general health. Methods: A cross-sectional observational study was conducted among 370 university students aged 19–25 years using the Revised Fibromyalgia Impact Questionnaire (FIQR) and EQ-5D-3L health questionnaire. Prevalence was calculated using diagnostic criteria thresholds. Regression analyses evaluated gradients between FIQR severity and general health domains. Results: Fibromyalgia prevalence was 27.0%, with higher rates in females (30.3%) than males (23.8%). Moderate-to-extreme pain was reported by 62.4%, and anxiety/depression by 61.3%. FIQR severity demonstrated significant regression gradients across mobility (R²=0.085), self-care (R²=0.160), usual activities (R²=0.103), pain/discomfort (R²=0.126), anxiety/depression (R²=0.156), and overall health status (R²=0.223; p<0.001). Conclusion: Fibromyalgia is highly prevalent among university students and substantially impairs physical and psychological health domains, with strongest effects observed in self-care and mental health. Early screening and integrated campus-based interventions are warranted.